Nicotinate O-Glucosylation Is an Evolutionarily Metabolic Trait Important for Seed Germination under Stress Conditions in Arabidopsis thaliana . Issue 7 (26th June 2015) - Li, Wei; Zhang, Fengxia; Chang, Yuwei; Zhao, Tao; Schranz, M. Eric; Wang, Guodong
Abstract : Nicotinate O -glucosylation, a Brassicaceae-specific metabolic trait, plays a key role in seed germination under stress conditions in Arabidopsis thaliana. Abstract: The glycosylation of nicotinate (NA ), a key intermediate of the NAD salvage pathway, occurs widely in land plants. However, the physiological function of NA glycosylation is not well understood in planta, and no gene encoding NA glycosyltransferase has been reported to date. NA glycosylation in Arabidopsis thaliana occurs at either the N - or the O -position of the NA molecule, and O -glucosylation appears to be unique to the Brassicaceae. Using gene-enzyme correlations focused on Family 1 glycosyltransferases (GTs; EC 2.4), we identified and characterized three Arabidopsis GTs, which are likely involved in NA glycosylation. These include one NA O GT (UGT74F2; previously identified as a salicylic acid glycosyltransferases) and two NA N GTs (UGT76C4 and UGT76C5). Arabidopsis mutants of UGT74F2 accumulate higher levels of free NA, but not salicylic acid, than that of the wild type, and this inversely correlated with seed germination rates under various abiotic stresses. The germination defect of the ugt74f2-1 mutant could be fully complemented by overexpression of UGT74F2 . These observations, together with comprehensive chemical analysis, suggest that NA glycosylation may function to protect plant cells from the toxicity of NA overaccumulation during seed germination. Combined with phylogenetic analysis, our results suggest that NA O GTs arose recently in the Brassicaceae family and may provide a fitness benefit. The multifunctionality of UGT74F2 in Arabidopsis is also investigated and discussed.